Letture anticanoniche della biofiction, dentro e fuori la metafinzione Il mondo 'possibile' di Mab's Daughters - Vannucci, Valentina (Biblioteca di Studi di Filologia Moderna, 2014)
Letture anticanoniche biofiction, dentro e fuori la metafinzione, aims at offering multiple interpretations to biofictions. For the critical analysis of these pieces, identified so far with a 'symptomatic' examination of various fictional texts on a given historical period or person, some possible non-canonical directions have been proposed: a 'horizontal' method, which brings biofiction into the 'fictional galaxy' of a writing subject (as in the case of Michèle Roberts), and then a 'vertical' method, which explores a model-biofiction to deconstruct and then reconstruct the intertwining of the synchronic and diachronic voices of its singular modus operandi. The final part of the volume is dedicated to Mab's Daughters by Judith Chernaik, an extremely interesting case of biofiction 'with possible worlds'. Letture anticanoniche della biofiction, dentro e fuori la metafinzione: The 'possible' world of Mab's Daughters by Vannucci, Valentina is licensed under a Creative Commons Attribution-Non-commercial-No Derivative Works 2.5 Italy License.Based on a work at www.fupress.com.